The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3171/2014.2.peds12508
|View full text |Cite
|
Sign up to set email alerts
|

Risk of radiation-induced malignancies from CT scanning in children who underwent shunt treatment before 6 years of age: a retrospective cohort study with a minimum 10-year follow-up

Abstract: Object A number of mathematical models predict the risk of future cancer from the ionizing radiation exposure of CT scanning. The predictions are alarming. Some models predict 29,000 future cancers and 14,500 deaths in the US will be directly caused by 1 year's worth of CT scanning. However, there are very few clinical data to justify or refute these claims. Young children are theoretically highly susceptible to the damaging effects of radiation. In this study, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
4
16
0
Order By: Relevance
“…[9] Interestingly, White et al also report high numbers of CT scans in children, with even higher rates in neonates and infants undergoing shunt insertion before the age of 1 year, compared with those whose shunt was inserted between 1 and 6 years of age. [37] This trend is reflected in our own data and is most probably due to a previously identified correlation between younger age at the time of shunt insertion and increased rates of malfunction and infection. [1,10] Of the children undergoing 'in house' CT head scans in our study, surgical intervention was observed following 31% of scans.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…[9] Interestingly, White et al also report high numbers of CT scans in children, with even higher rates in neonates and infants undergoing shunt insertion before the age of 1 year, compared with those whose shunt was inserted between 1 and 6 years of age. [37] This trend is reflected in our own data and is most probably due to a previously identified correlation between younger age at the time of shunt insertion and increased rates of malfunction and infection. [1,10] Of the children undergoing 'in house' CT head scans in our study, surgical intervention was observed following 31% of scans.…”
Section: Discussionsupporting
confidence: 63%
“…However, White et al performed a retrospective cohort study, including 104 children who underwent CSF shunt placement. In total, 1,584 CT head scans were performed over a 10year period, with no observed malignancies within the cohort [37]. Despite these findings appearing reassuring, there is strong epidemiological evidence linking CT scanning in childhood with an increased risk of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…22 White et al demonstrated that in children undergoing surveillance for shunt malfunction, the mean brain dose from a mean of 16.3 CT scans in the first year of life was 321 mGy, with no increase in the risk of malignancy over the 10-21 years of follow-up. 30 Consistent with this conclusion, the largest study of population-based risk of malignancy after radiation exposure by dose demonstrated no significant increase in the relative risk of malignancy after exposure to 0.01-9.99 Gy. 27 Additionally, neurological and nonneurological risks of DSA in the infant population were recently reviewed at our institution with no increase in morbidity in this population.…”
Section: Discussionsupporting
confidence: 67%
“…The appropriate follow-up modality and timing are therefore subjects of debate, particularly in light of concerns regarding radiation exposure and general anesthesia in children. 7,22,30 We present our experience with surveillance for AVM recurrence, associated risk factors, and clinical outcome, while considering the implications of these findings for follow-up protocols after treatment.…”
mentioning
confidence: 99%
“…One previous study (2009) claimed that approximately 29,000 future cancers could be related to 1 year of CT scan in the United States. 48 However, a recent study 49 published in 2014 claimed that zero radiationinduced malignancy were detected after routine CT scans. They evaluated 104 children who underwent cerebrospinal fluid shunt placement prior to the age of 6 years and with at least 10 years of follow-up data.…”
Section: Discussionmentioning
confidence: 99%